2017
DOI: 10.1007/s11920-017-0813-7
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Treatments for Eating Disorders and Obesity

Abstract: Purpose of Review Recent research has highlighted executive function and neurocognitive deficits among individuals with eating and weight disorders, identifying a potential target for treatment. Treatments targeting executive function for eating and weight disorders are emerging. This review aims to summarize the recent literature evaluating neurocognitive/executive function-oriented treatments for eating and weight disorders and highlights additional work needed in this area. Recent Findings Cognitive remed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 91 publications
(117 reference statements)
4
35
0
1
Order By: Relevance
“…Despite the broad pattern of deficits noted in this review there is comparatively limited research in EDs focused on cognitive training and examining the effectiveness of such treatments. While emerging theory and empirical evidence suggests various neurocognitive processes may be modifiable through interventions (e.g., Boutelle, Monreal, Strong, & Amir, 2016; Eichen, Matheson, Appleton-Knapp, & Boutelle, 2017; Jones et al, 2016; Koffarnus, Jarmolowicz, Mueller, & Bickel, 2013; Tchanturia et al, 2014), much of this research in EDs is preliminary and has been limited to small samples. For example, initial findings suggest that attention bias modification (ABM) may lead to improvements in binge eating and other ED symptoms (Boutelle et al, 2016), and a recent meta-analysis demonstrated that single-session inhibitory control training (ICT) led to significant decreases in food and alcohol choices or consumption in a laboratory study (Jones et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the broad pattern of deficits noted in this review there is comparatively limited research in EDs focused on cognitive training and examining the effectiveness of such treatments. While emerging theory and empirical evidence suggests various neurocognitive processes may be modifiable through interventions (e.g., Boutelle, Monreal, Strong, & Amir, 2016; Eichen, Matheson, Appleton-Knapp, & Boutelle, 2017; Jones et al, 2016; Koffarnus, Jarmolowicz, Mueller, & Bickel, 2013; Tchanturia et al, 2014), much of this research in EDs is preliminary and has been limited to small samples. For example, initial findings suggest that attention bias modification (ABM) may lead to improvements in binge eating and other ED symptoms (Boutelle et al, 2016), and a recent meta-analysis demonstrated that single-session inhibitory control training (ICT) led to significant decreases in food and alcohol choices or consumption in a laboratory study (Jones et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the role of reward and of attention control in relation to food in people with obesity and/or binge eating disorder (BED), an eating disorder leading to (and often comorbid with) obesity. These studies show enhanced reward sensitivity when participants are presented with food cues (both neurally and self-reported), and lower self-regulatory processing (8,9). Relatedly, some studies have reported the presence of attention biases to food and other salient cues in obesity and BED (10,11) presumably due to low attention control for highly rewarding stimuli (e.g.…”
Section: Introductionmentioning
confidence: 93%
“…Several studies have investigated the role of reward and of attention control in relation to food in people with obesity and/or binge eating disorder (BED), an eating disorder leading to (and often co-morbid with) obesity. These studies show enhanced reward sensitivity when participants are presented with food cues (both neurally and self-reported) and lower self-regulatory processing [8,9]. Relatedly, some studies have reported the presence of attention biases to food and other salient cues in obesity and BED [10,11] presumably due to low attention control for highly rewarding stimuli (e.g.…”
Section: Introductionmentioning
confidence: 94%